Inter Subregional forum for enhanced implementation of the world trade organization trade facilitation agreement summary of proceedings. (Asian Development Bank, 2019)
Global implementation of the TFA promises to reduce trade costs between 6% and 16% and benefit small and medium sized enterprises for inclusive growth. Held in October 2018, the Inter Subregional Forum on Enhanced Implementation of the World Trade Organization Trade Facilitation Agreement involved discussions on success stories and common challenges shared by government officials responsible for leading and guiding notification and implementation of the TFA in ADBs member economies and subregional programs.